Prevalence and Quantity of Gastrointestinal Parasites in Sows of Ban Na Chakwai Famers in Phitsanulok Province - มูลสาร, ปรีชา; มูลสาร, ยิ่งลักษณ์; เสาเขียว, จิตราวรรณ; จันทรา, พนิดา; แสงแผน, ไตรภพ (Journal of Mahanakorn Veterinary Medicine, 2019)
The purposes of the study were 1) to study general information of sow farmers and farming conditions and 2) to survey the prevalence of gastrointestinal parasites of sows in Ban Na Chakwai, Phitsanulok province. The general information and farming condition of 20 farmers were collected by interview. Fecal samples were collected from 96 sows to examined parasite eggs by Simple floatation technique, Simple sedimentation technique and Modified McMaster technique. It was found that most of the farmers were female (80.00 %), in age of 50-60 years (60.00 %), raising 1-5 of Large White - Landrace sows/farm (70.00 %). Several types of mixed feed were used: 1) concentrate + broken rice 2) rice bran 3) rice bran + banana stalk + native water spinach and 4) rice bran + food waste. The mixed of rice bran + banana stalk + native water spinach was mostly used (48.96 %). Sows were raised in different floor pens: 1) concrete floor 2) slatted floor (85.42 and 14.58 %, respectively). The prevalence of Isospora suis, Ascaris suum, Strongyloides ransomi and Trichuris suis were 100.00, 10.42, 3.13 and 1.04 %, respectively. The quantity (average egg/oocyte per gram; EPG/OPG) of five species was I. suis (5,330.1±97.9 OPG), A. suum (101.9±5.3 EPG), S. ransomi (9.2±0.7 EPG) and T. suis (1.0±0.1 EPG). It was indicated that, in small farmer condition without parasite control, the mild prevalence of gastrointestinal parasites in sows were common.